Phenomenological Characterization of Low-Potency Homeopathic Preparations by Means of Pattern Formation in Evaporating Droplets - Kokornaczyk, Maria Olga; Würtenberger, Sandra; Baumgartner, Stephan (Homeopathy, 2019)
Background Evaporation-induced pattern formation in droplets has been applied to test effects of high potencies. Here we propose for the first time the droplet evaporation method (DEM) as a tool to characterize low potencies on a qualitative and quantitative basis.Materials and Methods The present investigation consisted of: (1) screening of 18 different substances of mineral, vegetal, and animal origin in the 1x to 6x potency range; choice of four substances with characteristic pattern-forming properties; (2) replication experiments aiming at the differentiation of four homeopathic preparations at the same potency levels (2x–6x); and (3) control experiments performed on three preparations. The DEM experimental protocol consisted of the evaporation of droplets of the analyzed potency per se, placed on microscope slides and in controlled conditions. The resulting patterns were photographed and subjected to computerized image analysis.Results The screening experiments yielded a wide variety of patterns. Homeopathic preparations of mineral origin showed the largest variety of forms, whereas potencies of vegetal origin mostly created dendritic patterns, probably due to diffusion-limited aggregation. The here-analyzed image analysis variables (gray-level distribution, entropy, and inverse difference moment) allowed a highly significant differentiation of patterns prepared from four substances (Echinacea, Baptisia, Luffa, and Spongia) at the same potency levels in the range 2x to 4x, whereas patterns obtained from potencies 5x and 6x could no longer be differentiated and resembled the pattern of pure solute (purified water). The control experiments showed reasonable experimental model stability.Conclusions DEM seems to be a promising tool for qualitative phenomenological characterization of homeopathic preparations in low potency. We propose the application of the current experimental model for investigating further research topics in this field, such as the comparison of potencies versus simple dilutions or the contribution of component remedies to the patterns formed by homeopathic combination medicines.
Keywords: droplet evaporation method; crystallization patterns; homeopathy; mineral extracts; vegetal extracts; low potencies